‘AZL (COITUS INTERRUPTUS) DALAM PANDANGAN FUKAHA - La Ode Ismail Ahmad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2010)
This article copes with the issue of ‘azl from Islamic perspective. Generally, ‘azl is the prevention of pregnancy by releasing the sperm out of vagina. In modern context, this practise is analogous with the family planning. The only difference is that the modern family planning uses medicines. Islamic scholars, basing their respective arguments on some hadits of the prophet, have different opinion on the issue: some of them permit the practise of ‘azl, while some others prohibit it. This study reveals that the hadits used by Islamic scholars who forbid the practise of ‘azl is dha’if. Therefore, the practise of ‘azl is actually permitted, with the permission of wife, and without permission if applied to slave.